The classic : Sainte-Beuve and the nineteenth-century culture wars - Prendergast, Christopher (Oxford University Press, 2007)
Focusing on a moment and a source in nineteenth-century France, Christopher Prendergast takes up a big question that is still with us: What is a classic? The question is, by virtue of its insistent recurrence, itself a classic question. It returns to haunt us. It provided the title of a text for French critic Charles-Augustin Sainte-Beuve in 1850 ("Qu'est-ce qu'un classique?"), as it did in the twentieth century for T.S. Eliot and John Coetzee. Centring on Sainte-Beuve in his nineteenth-century context, Prendergast's inquiry takes us historically to many places (antiquity, the middle ages, the seventeenth and eighteenth as well as the nineteenth and early twentieth centuries). He also provides an intellectual history that travels across multiple disciplinary territories (in addition to literary criticism and literary history, classical studies, comparative philology, historiography and political thought).